Implementasi Metode Scrum Dan Analisis Swot Sebagai Strategi Framework Customer Relationship Management (CRM) Pada Perusahaan Aqilla Rent Car Semarang - Daniel Adi Setya Rahardjo (Institut Nalanda, 2023)
Main problem: implementation of the scrum method and swot analysis as a customer relationship management (crm) framework strategy at the aqilla rent car company semarang. Objective: analyze and apply the schrum and swot methods as crd at the aqilla rent car company semarang. Originality: implementation of the scrum method and swot analysis as a customer relationship management (crm) framework strategy at the aqilla rent car company semarang. Method: the research method uses the schrum method and swot analysis. Results: judging from the methodology structure, the crm system is proposed to provide attributes that help clients make it easier to place orders.